INSULIN SECRETAGOGUE EFFECT OF ROOTS OF RAVENALA MADAGASCARIENSIS SONN. - AN IN VITRO STUDY - PRIYADARSINI S, SAKTHI; PR, KUMAR; ANAND, ABHISHEK; B, DEVENDIRAN; S KADIYAM, VENKAT; PADMANABH ROY, RICHIE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to establish the cytotoxicity profile and to evaluate the insulin secretagogue effect of ethanolic root extract of Ravenala madagascariensis Sonn. Methods: The cell viability of rat insulinoma 5F (RIN5F) cell lines over the treatment of plant extract was assessed by 3-(4,5-dimethyl-2-thiazolyl)- 2,5-diphenyltetrazolium bromide assay. The insulin-releasing effect was evaluated by insulin secretion assay over RIN5F cell lines by enzyme-linked immunosorbent assay. Results: The ethanolic extract of the roots of R. madagascariensis Sonn. showed negligible cytotoxicity at 20–40 μg/ml, and hence, concentrations up to 40 μg/ml were used in insulin secretion assay. The ethanolic root extract at 20 and 40 μg/ml significantly (p<0.05 compared to control) stimulated the insulin release in a dose-dependent manner even in the presence of glucose at lower and higher concentrations (5 and 10 mM). Conclusion: Thus, our results validate its traditional claim in the treatment of diabetes by stimulating the secretion of insulin, thereby suggesting a possible mechanism of its antidiabetic effect.